Philosophy and Institutions: A Constant Dialogue (Nóema, 2023)
The position and role of philosophy in universities has always been a subject of interest, particularly on the part of the holders of the discipline, who are evidently convinced of its special status within the educational curriculum. This article briefly examines the positions of a number of philosophers who have explicitly expounded on this subject, from Kant to Heidegger, from Ortega y Gasset to Martha Nussbaum, as illustrious witnesses of the indispensability of the contents and methods of philosophy for every field of knowledge, all the more so today, when the usefulness of humanistic thought is being disavowed in favour of an increasingly technical and specialised education.
Keywords: Philosophy; Institutions; University; Education; Humanities